Some aspects of economic and legal responsibility - Шишка, Роман Богданович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article refers to the economic and legal liability as to judicial sanctions against the perpetrator in the commission of an offense which infringes the economic order. The author assumes that the problem is that: 1) the term "liability" and its derivatives, including economic and legal, are considered primarily in a broad sense as any sanctions against the offender; 2) such application, which is associated with the protection of the rights and/or punishment of a guilty or responsible person, relating to the administration of justice; 3) sanctions should be applied only in the manner and procedure established by legislation; 4) according to Art. 124 of the Constitution of Ukraine it’s defined at the imperative level that the enforcement of justice belongs to the exclusive jurisdiction of the courts; 5) legislative acts, administrative and especially those that implement it (economic, environmental, etc.) provide extra-judicial sanctions; 6) in the doctrine of law such a blatant contradiction under the rule of law is dropped or reduced to the right of government to impose sanctions. Conceptual approaches to the legal liability: penalties, sanctions, public pressure and undergoing can be variously interpreted and serve as a basis for the imperative (narrow) or discretionary (wide) explication of legal liability. The author supports the sanction concept, but points out that the application of responsibility is a prerogative of the court, and the implementation of the sanctions is possible by other organs of the state, but it is a kind of prejudicial impact on the offender that has its positive features. It is against Constitution and inappropriate to lower the level of justice to extrajudicial one. In the application of penalties out of the court it is not about additional costs of offender as in judicial economic and legal responsibility. Attention is paid to the problem of understanding the escalation of economic offense’s obligation in the economic liability. For the legal liability’s use it’s necessary to go to the court (lawsuit) with the request to apply to the offender coercion in the form of sanctions and to make a decision regarding his prosecution. The input of administrative proceedings mediation on economic abuse is reasoned. The need to overcome the stereotype of a broad understanding of economic and legal responsibility is advocated; the grounds of undoubted and disputed penalties’ selection for offenses, which are provided in the norms of economic law in a specific order, are given.